Development and Maturation of the Pink Fungus (Upasia salmonicolor) Stages in Java - Ambarwati-Harsojo Tjokrosoedarmo (Universitas Gadjah Mada, 1996)
The development of the pink fungus stages showed that among the five stages, cobweb stage is the most important, since this stage may form the other four stages. I. Cobweb stage, develops following the germination of either basidiospores or conidia both on exposed and shaded side of branches. II. Pseudonodular stage, develops from symphogenous aggregation of cobweb stage mycelia on the surface of lenticel or cracks on shaded bark. III. Teleomorph, develops in two ways: a. Teleomorph incrustation develops from cobweb stage mycelia through four layers: basal layer, intermediate layer, subhymenial layer, and hymenial layer; b. Teleomorph pustule, develops from pseudonodular stage, through four layers, mirror to teleomorph incrustation. IV. Nodular stage, develops from meristogenous aggregation of cobweb stage mycelia on exposed bark. V. Anamorph, develops in two ways: a. From nodular stage; b. From cobweb stage mycelia on exposed bark.